Morris Ranger: The Rise and Fall of the Liverpool Cotton Market's Greatest Speculator, 1835 to 1887. (1st January 2021) - Hall, Nigel
Abstract : In the period 1878 to 1883 there was heavy speculation in the Liverpool raw cotton market associated with a trader named Morris Ranger. Little has previously been written about Ranger and his background. Ranger was born in Germany and emigrated to the United States in 1855. He initially traded in tobacco but branched out into cotton during the American Civil War. He settled in Liverpool in 1870. His cotton speculations were enormous, but he fell bankrupt in 1883. The speculations associated with Ranger involved other Liverpool traders and drew heavy criticism from the spinning industry. The speculations played a part in a reorganisation of the Liverpool market and attempts to circumvent it, including the building of the Manchester Ship Canal.